2022
DOI: 10.1186/s13024-022-00560-w
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 is a neuronal receptor for α-synuclein uptake and spread

Abstract: Background The aggregation and spread of α-synuclein (α-Syn) protein and related neuronal toxicity are the key pathological features of Parkinson’s disease (PD) and Lewy body dementia (LBD). Studies have shown that pathological species of α-Syn and tau can spread in a prion-like manner between neurons, although these two proteins have distinct pathological roles and contribute to different neurodegenerative diseases. It is reported that the low-density lipoprotein receptor-related protein 1 (LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 71 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…Recent studies indicated an essential role of low-density lipoprotein receptor-related protein 1 (LRP1) in α-synuclein spreading between cells [ 54 ]. LPR1 is a highly expressed central nervous system protein receptor involved in intracellular signaling and endocytosis.…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated an essential role of low-density lipoprotein receptor-related protein 1 (LRP1) in α-synuclein spreading between cells [ 54 ]. LPR1 is a highly expressed central nervous system protein receptor involved in intracellular signaling and endocytosis.…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
“…It is located predominantly in the plasma membrane. Chen et al [ 54 ], using LRP1 knockout (LRP1-KO) induced pluripotent stem cells (iPSCs), demonstrated that LRP1 is a vital regulator of α-synuclein neuronal uptake and mediator of its spread in the brain. LRP1 binds to the N-terminus of α-synuclein through lysine residues, being a key regulator for the endocytosis of both monomeric and oligomeric forms of α-synuclein.…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
“…αSyn fibrils can spread from cell to cell, contributing to pathogenicity [ 140 , 141 ]. LRP1 was recently shown to be a key regulator of αSyn neuronal uptake, as well as an important mediator of αSyn spread in the brain [ 17 ]; previously it was mainly known to regulate the spread of tau proteins [ 142 ]. At the same time, the expression of LRP1 is lowered in the brain endothelial cells of PD patients, breaking the maintenance of the BBB [ 143 ].…”
Section: α-Synuclein In Health and Parkinson’s Diseasementioning
confidence: 99%
“…This is facilitated by the expression of inflammatory cytokines that disrupt the blood–brain barrier (BBB) [ 16 ]. Other factors than inflammatory cytokines, e.g., cell membrane receptors, such as low-density lipoprotein receptor-related protein 1 (LRP1), lymphocyte activation gene 3 (LAG3) and amyloid precursor-like protein 1 (APLP1) are involved in cell-to-cell transmission [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors then established a murine model that discriminates between neurons transduced with the adeno-associated virus expressing human α-syn and neurons that receive human α-syn through spreading. Using this novel model, they demonstrated that the deletion of LRP1 in the neurons suppresses the transmission of human α-syn in mice [ 8 ].…”
mentioning
confidence: 99%